2020
DOI: 10.1002/jsid.866
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of visual fatigue under LED tunable white light with different blue components

Abstract: Light‐emitting diode (LED) light source has high intensity emission of blue components absent in the daylight spectra and regulates human physiology and behavior. The aim of this study was to explore the effects of LED tunable white light with different blue‐component intensities on visual fatigue based on human eye photoreceptors. The short (S)‐cone and melanopsin illuminance were about 212% and 82% higher for blue‐enriched white light than blue‐less white light, respectively. The photopic illuminance was sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Luminance between scenes in HMDs should be harmonized to avoid very different brightness leading to higher discomfort (Ha et al, 2020) Apply dark mode with compensated luminous intensity (Vasylevska et al, 2019) Calibration of HMDs' screens (Toscani et al, 2019) Patterson ( 2009) advise interocular luminance differences and interocular contrast differences at less than 25% VF_7 VII Blue light (range from 400 to 490 nm) Blue light implies less accommodation (Panke et al, 2019). It can impact (Anses, 2019) myopia (positive or negative) and dry eye syndrome It induces visual fatigue (Rabin et al, 2020;Zhang et al, 2020b). 480 to 490 nm disturb circadian rhythms during the evening, impacting sleep (Wahl et al, 2019), making users more susceptible to visual fatigue (Munsamy and Chetty, 2020) Reducing blue light with a filter (Chiu and Liu, 2020).…”
Section: Guidelinesmentioning
confidence: 99%
“…Luminance between scenes in HMDs should be harmonized to avoid very different brightness leading to higher discomfort (Ha et al, 2020) Apply dark mode with compensated luminous intensity (Vasylevska et al, 2019) Calibration of HMDs' screens (Toscani et al, 2019) Patterson ( 2009) advise interocular luminance differences and interocular contrast differences at less than 25% VF_7 VII Blue light (range from 400 to 490 nm) Blue light implies less accommodation (Panke et al, 2019). It can impact (Anses, 2019) myopia (positive or negative) and dry eye syndrome It induces visual fatigue (Rabin et al, 2020;Zhang et al, 2020b). 480 to 490 nm disturb circadian rhythms during the evening, impacting sleep (Wahl et al, 2019), making users more susceptible to visual fatigue (Munsamy and Chetty, 2020) Reducing blue light with a filter (Chiu and Liu, 2020).…”
Section: Guidelinesmentioning
confidence: 99%
“…However, a similar study conducted by Yuda et al 28 showed that in exposure to red, blue and green monochromatic LED light sources, HF decreased in blue light. In a study by Zhang et al, 29 exposure to LED light sources with CCTs of 2850 K and 6395 K, led to increased LF and LF/HF under the higher CCT, but no changes in HF.…”
Section: Introductionmentioning
confidence: 93%
“…A study by Litscher et al 86 investigated the effects of different red (631 nm) and blue (456 nm) lights producing 140-lx illuminance for 10 min during the daytime at rest, and found that exposure to blue light increased LF/HF. Another study by Zhang et al 29 investigated the effects of a blue-enriched LED light source (6395 K and 227 lx) and blue-depleted light source (2850 K and 232 lx) for 30 min of exposure during a daytime study task and showed that exposure to the blue-enriched light increased LF/HF. Similar results were obtained by Yuda et al 64 who investigated blue, green and white lights at different melanopic photon flux densities for 10 min during the daytime at rest and found that exposure to 'bluer' light decreased HF.…”
Section: Effect Of Cct On Hrv Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The subjective evaluation contains exploratory research [5], psychophysical scale research [6] and subjective questionnaire [7][8][9][10]. Common physiological parameters of visual fatigue research include electroencephalogram (EEG) [11], electrocardiogram (ECG) [12], galvanic skin responses (GSR) [13], photoplethysmographic (PPG) [14], skin temperature (SKT) [15] and eye movement parameter [16]. An important manifestation of visual efficacy decreases when visual fatigue occurs, such as ophthalmological parameters [17].…”
Section: Introductionmentioning
confidence: 99%